Wine, beer and Chinese Baijiu in relation to cardiovascular health: the impact of moderate drinking - Qiao Kang; Jinyuan Sun; Bowen Wang; Baoguo Sun (Food Science and Human Wellness)
Excessive alcohol consumption (≥15 drinks per week) causes chronic diseases and multiple other health conditions. Nevertheless, alcohol beverages have been used as a vital medicine ingredient in various cultures since ancient times. A wealth of epidemiological and experimental research has shown that light-moderate alcohol consumption, regardless of beverage type, is associated with reducing cardiovascular incidence and mortality rate. Due to the disparities in raw materials, fermentation techniques, production environment, etc., alcoholic beverages tend to possess different non-ethanol component profiles, thus resulting in varying degrees of health effects. Furthermore, bioactive compounds in alcohol are continuously discovered as well as the mechanisms underlying their cardioprotective contributions at a molecular level. This article elucidates the epidemiology of moderate alcohol consumption and various cardiovascular conditions, along with the limitations and controversies of current studies. In addition, protective effects and putative mechanisms of both ethanol and non-ethanol components of wine, beer, and Chinese Baijiu, the three most representative alcoholic beverages worldwide, are to be evaluated within the context of a rational drinking pattern.